MENUMBUHKAN SIKAP RAMAH LINGKUNGAN MAHASISWA MELALUI PEMBELAJARAN PENGETAHUAN LINGKUNGAN BERBASIS SCIENTIFIC APPROACH - Atip Nurwahyunani (Universitas PGRI Semarang, 2015)
Environmental education was one?óÔé¼Ôäós the important factor to successedin Environmental management, it?óÔé¼Ôäós also important material humanresources to carried out sustainable development. Scientific Approachwas used in scientific methods teaching and learning. This approachwas expected to made students thought scientific, logic, critical, andobjective. The purpose of this research was created an innovativelearning through Scientific Approach. The subject for this researchwas class 2C, D, and E, of Biology Departement, PGRI SemarangUniversity. It?óÔé¼Ôäós used independent variable and it?óÔé¼Ôäós also used researchand development (R&D) with modifications. Analyzed data used amixed-method descriptive quantitative and qualitative. The analysisshowed that all variants had same P valued 0.885> 0,05 so H0accepted. H0 means the receipt of a third variant equal orhomogeneous. ANOVA results obtained F count 9.690 compared withFtable with 95% (5% error rate) on the DF1 (number of variable-1) = 2,and DF2 (n-3) or 117-3 = 114, results obtained Ftabel amounted to3.076. Fhitung value> Ftable (9.690> 3.076), then H0 is rejected. It couldbe concluded, there were difference test scores in first class, secondclass and third class.Keywords: environtment education, scientific approach, eco-friendlyattitude